2017
DOI: 10.5334/snr.85
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities in Nonreligious and Religious Older Adults in the United States: A Descriptive Epidemiology of 16 Common Chronic Conditions

Abstract: In this paper, we compute prevalence estimates for nonreligious and religious people in relation to 16 common chronic conditions in contemporary American society. Using survey data from the National Social Life, Health, and Aging Project, we speak to current debates concerning potential relationships between religion, nonreligion and health in older adult populations with two key findings. First, we show no consistent relationships between religion or nonreligion and chronic condition prevalence. Second, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Studies looking at affiliation have often found that being nonaffiliated is not associated with self-reported measures of health. [31][32][33] Studies that differentiated between different types of nonaffiliation (atheists, agnostics, nonreligious, etc) found that these effects are complex, often with some nonaffiliated groups having better health outcomes than other nonaffiliates and the religiously affiliated. 31,32,34,35 Recent studies using European population data from the Survey of Health, Aging and Retirement in Europe (SHARE) found that religious education and participation in a religious organization are associated with lower rates of noncommunicable diseases, disabilities, depressive symptoms, health behaviors, and poor self-rated health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies looking at affiliation have often found that being nonaffiliated is not associated with self-reported measures of health. [31][32][33] Studies that differentiated between different types of nonaffiliation (atheists, agnostics, nonreligious, etc) found that these effects are complex, often with some nonaffiliated groups having better health outcomes than other nonaffiliates and the religiously affiliated. 31,32,34,35 Recent studies using European population data from the Survey of Health, Aging and Retirement in Europe (SHARE) found that religious education and participation in a religious organization are associated with lower rates of noncommunicable diseases, disabilities, depressive symptoms, health behaviors, and poor self-rated health.…”
Section: Discussionmentioning
confidence: 99%
“…That scores on physical function measures do not differ by religious affiliation is in line with the literature on religious affiliation and health. Studies looking at affiliation have often found that being nonaffiliated is not associated with self‐reported measures of health . Studies that differentiated between different types of nonaffiliation (atheists, agnostics, nonreligious, etc) found that these effects are complex, often with some nonaffiliated groups having better health outcomes than other nonaffiliates and the religiously affiliated …”
Section: Discussionmentioning
confidence: 99%